Domestic Distributional Roots of National Interest - Lee, Soyoung (American Political Science Review, 2024)
What international issues become national interests worth fighting for, and why? Contrary to conventional wisdom, I argue that issues without clear economic value, such as barren lands, are more likely to be perceived as national interests because they do
Keywords: Domestic Distributional Roots; Economic Value; National Interest; Politicians